1995
DOI: 10.1111/j.1365-3121.1995.tb00802.x
|View full text |Cite
|
Sign up to set email alerts
|

A high‐velocity layer in the lower crust of the North German Basin

Abstract: A network of deep seismic refraction profiles in Northern Germany consisting of parts of the European Geotraverse (EGT) and additional new Unes is interpreted. The most striking result is the proof of an approximately 10 km thick high‐velocity layer in the lower crust. Its P‐wave velocity of 6.9‐7.5 km s−1 is typical for shield crusts or lower crust in extensional environments intruded by mafic magma. The layer is observed in an area of roughly 150 × 180 km north of the Elbe river and seems to continue north‐e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 24 publications
3
30
1
Order By: Relevance
“…However, in the text, Hoffman, Stiewe & Pasternak (1996) somewhat puzzlingly suggest that the significant differences in Moho depth reported by Thybo et al (1990) across the TransEuropean Fault are not confirmed by their study, although their figure 5 and supporting data would appear to contradict this statement. Rabbel et al (1995) reported an area of increased crustal thickness in the region of the Ringkøbing-Fyn High which corresponds to a c. 7 km deepening of the Moho. They suggest that the southern boundary of this Moho low corresponds with the postulated Trans-European Fault trend.…”
Section: C Geophysical Evidencementioning
confidence: 98%
See 1 more Smart Citation
“…However, in the text, Hoffman, Stiewe & Pasternak (1996) somewhat puzzlingly suggest that the significant differences in Moho depth reported by Thybo et al (1990) across the TransEuropean Fault are not confirmed by their study, although their figure 5 and supporting data would appear to contradict this statement. Rabbel et al (1995) reported an area of increased crustal thickness in the region of the Ringkøbing-Fyn High which corresponds to a c. 7 km deepening of the Moho. They suggest that the southern boundary of this Moho low corresponds with the postulated Trans-European Fault trend.…”
Section: C Geophysical Evidencementioning
confidence: 98%
“…Such evidence includes the increased crustal velocities in the area extending from the Baltic Shield to the Elbe Lineament (Rabbel et al 1995). There is a sharp velocity contrast in the lower crust between the regions southwest and northeast of the Elbe Lineament (Rabbel et al 1995;Thybo, 1990). To the southwest the velocities range from 5.9-6.6 km/sec, and increase in the northeast up to 6.9-7.5 km/sec.…”
Section: C Geophysical Evidencementioning
confidence: 98%
“…This fault system is part of the Elbe Lineament (Fig. 1), a regionally important structure which separates crustal domains of differing physical properties (Rabbel et al 1995;Tanner and Meissner 1996). Along the Elbe Lineament strike-slip movements during the Variscan orogeny were followed by oblique thrusting culminating in the Upper Cretaceous related to collisional processes in the Alps (Schretzenmayr 1993;Ziegler 1990).…”
Section: Geological Framework and Stratigraphymentioning
confidence: 99%
“…Seismic data indicate a high-velocity lower part of the crust in the TESZ in Germany, interpreted to be due to abundant mafic intrusions (Rabbel et al, 1995;Bayer et al, 2002;Thybo, 1997Thybo, , 2000. The SW limitation of this crust is the Elbe line (Aichroth et al, 1992).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The The lower crust of the P1 profile is seismically a continuation of that of the EEC (Guterch et al, 1994;Rabbel et al, 1995;Jensen et al, 1999;Grad et al, 2002Grad et al, , 2003. However, the heat flow in the area of the TESZ and adjoining parts of the Variscan Orogen is significantly higher.…”
Section: Relationships Between Seismic Properties and Lithologymentioning
confidence: 99%